Prospects and Challenges of Musharakah and Musharakah Mutanaqisah Financing in Islamic Microfinance: Case Studies of Indonesia and Malaysia - Norma Md Saad; Qurroh Ayuniyyah (Department of Islamic Economics, IPB University, 2026)
Musharakah, a unique Islamic mode of financing, involves joint contributions of capital and labor by both financier and entrepreneur. This profit and loss sharing (PLS) contract is considered one of the most ideal Islamic financing models, embodying the principles of cooperation and partnership. A specific application of this model is the diminishing partnership contract, known as Musharakah Mutanaqisah (MM). This study explores the implementation of musharakah and MM in Islamic microfinance through a qualitative comparative case study of two institutions: Bank Pembiayaan Rakyat Syariah (BPRS) Amanah Ummah Bogor, Indonesia, and Entrepreneurship Development Program (i-Taajir) under the Centre for Islamic Economics IIUM-CIMB Islamic Bank, Malaysia. Data were collected through interview, financial reports, institutional documents, and secondary sources, and analyzed thematically. The findings reveal that while both institutions apply musharakah-based financing to empower micro-entrepreneurs, they face challenges related to risk management, regulatory frameworks, and limited client understanding. Managerial implications suggest the need for better financial literacy programs, internal capacity building, and policy support to optimize musharakah implementation in microfinance settings. This study offers recommendations for enhancing the sustainability and operational effectiveness of equity-based Islamic financing models in the microfinance sector.